Penerapan Disiplin Pegawai Negeri Sipil Di Pengadilan Negeri Ambon - Hesty Kusumaningsy Ely; Salmon Eliazer Marthen Nirahua; Dezonda Rosiana Pattipawae (Pattimura Legal Journal)
Introduction: The position of civil servants has a strategic role in governance. Civil servants as an instrument of government are very central because they carry and carry out components of government regulations and policies to realize the goals of the state. In order to effectively prevent the occurrence of irregularities in the implementation of duties or violations of the behavior of court officials, it is necessary to carry out continuous supervision and guidance by each direct superior to his subordinates.